A study on the effeciency of reference librarians in UP Diliman in providing answers to reference questions - Ko, Stephen T.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Reference service done by librarians, is the process of helping library users identify sources of information in response to a particular question or query. Librarians are said to be one of the best if not the best, source of information or answers in any queries. With the emergence of today's technology, are the librarians still as efficient as they were before? Or do they just depend on the technology thus leading in the degradation of their credibility? Which is a better source between libraries and the internet search engines today? Why bother going to libraries if we have Google?
This is a study regarding the efficiency of reference librarians in UP Diliman in providing answers to reference questions. The study aims to determine the efficiency of reference librarians using the combination of the two factors, accuracy and time response. The study aims to determine how reliable the answers we get from UP Diliman librarians are. The study also aims to determine how quick librarians cater the information needs of the students. The study is a descriptive and experimental type of study. The types of reference questions commonly asked by the students of UP Diliman will be determined through survey questionnaires and the efficiency of reference librarians will be determined through conduct a test.
The result show that a lot of students ask general information types of questions and the least are organizational type of questions. There are only few of the types of questions stated in the study were being asked by the students. Regarding the performance of the librarians, there were some librarians that have rejected the queries of the researcher due to loads of tasks aside from reference service. They have also recommended to just using Google for the queries. For those who answered the queries, they gathered an excellent score in accuracy as well as the time response thus leading to efficiency. Of course, they were no faster than search engines but they managed to provide answers in an acceptable phase.
It can be concluded after the study that there are some libraries with no specific reference librarians and just have a rotational reference service job; this is a big problem since they tend to do other tasks also and reference service experience is a big key towards being an efficient reference librarian. Almost every librarian interviewed claimed that there are fewer reference queries ever since the emergence of search engines began. Some were even shocked in seeing such ready reference questions for all they were used to do was to provide books based on the subject. Librarians are still efficient today in cases wherein they entertain questions but become very inefficient when they become too busy to entertain queries. The researcher also concludes that in case of direct to the point ready reference questions such as "What is the capital of the Philippines?" it is better to use search engines for an efficient time management but when it comes to research questions like "Define librarianship" it is always libraries that can provide a better source than the internet for it is more authoritative, detailed, and complete.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Reference librarians -- Philippines